A study of frequency radiation of human torso for gender classification - Siti Zura, A. Jalil; Mohd Nasir, Taib, Prof. Dr.; Hasnain, Abdulllah@Idris; Megawati, Mohd Yunus (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/